A COMPARATIVE STUDY OF GANDHI’S COLLABORATION AND RESISTANCE IN THE FIRST AND SECOND WORLD WARS - Kumari, Kirti (International Journal of Research -GRANTHAALAYAH, 2025)
This paper presents a comparative analysis of the significant strategic and ideological shifts in Mohandas Karamchand Gandhi’s attitude toward the British Raj during World War I (1914-1918) and World War II (1939-1945). During World War I, Gandhi encouraged Indians to join the army, adopting a policy of conditional collaboration with the British Empire. He believed that proving loyalty would lead to self-rule (Swaraj) for India after the war. However, the British government’s repressive laws like the Rowlatt Act and its neglect of the demand for self-rule shattered Gandhi’s faith in British justice. In contrast, with the advent of World War II, Gandhiji offered full resistance to the British war effort and called for the Quit India Movement (1942). This shift reflected his increased understanding of the true nature of imperialism and the strengthening of his principle of nonviolence. This study examines the causes, manifestations, and decisive impact of this ideological evolution from collaboration to resistance on the Indian independence movement.